Analysis Of The Meaning And Nature Of Islamic Culture - Muhammad Nawawi; Haidar Putra Daulay; Sholihah Titin Sumanti (Jurnal Multidisiplin Sahombu, 2025)
Research This to study analysis meaning and essence Islamic culture through approach studies library qualitative with analyze various source literature history . This study aiming For understand draft base Islamic culture , the differences with civilization , as well as explore essence Islamic culture in context Muslim life . Research results show that Islamic culture (al- Tsaqafah ) has difference meaning  with civilization (al- Hadharah ), where culture covers method thinking and feeling that states self in all over aspect life Muslim society , while civilization refers to more aspects​ proceed in form knowledge knowledge , technology , and art . The essence Islamic culture lies in integration between religious teachings and practices life everyday life based on the Qur'an and Hadith, including elements important like religious teachings , art , science knowledge , system social , as well as traditions and customs . Research this also reveals that Islam is not is results from culture , but rather religion that builds and gives birth to field based on the idea the values of monotheism and aims For welfare people man.